Adaptation of Sexual Intercourse between Sharia and Law - Hussein Fayyad, Abbas; Ismael Ibrahim Al-Mamoori, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The philosophy of criminalization differs between Sharia and law. At a time when Islamic Sharia views sexual intercourse outside of marriage as an assault on a public right or public interest and is considered one of the five basic interests in society and is the interest of birth control, unlike the philosophy of law that is completely different from Sharia Criminalization of unlawful sexual intercourse, as it regards it as an assault on a personal right, which is sexual freedom that allows its owner to have sexual intercourse when he so desires, provided that this practice with the other party has occurred with the consent of adults of adulthood and without marital marriage.